Hydrogen sorption kinetics, hydrogen permeability, and thermal properties of compacted 2LiBH4MgH2 doped with activated carbon nanofibers. (7th June 2019) - Thiangviriya, Sophida; Sitthiwet, Chongsutthamani; Plerdsranoy, Praphatsorn; Capurso, Giovanni; Pistidda, Claudio; Utke, Oliver; Dornheim, Martin; Klassen, Thomas; Utke, Rapee
Abstract: To improve the packing efficiency in tank scale, hydrides have been compacted into pellet form; however, poor hydrogen permeability through the pellets results in sluggish kinetics. In this work, the hydrogen sorption properties of compacted 2LiBH4 MgH2 doped with 30 wt % activated carbon nanofibers (ACNF) are investigated. After doping with ACNF, onset dehydrogenation temperature of compacted 2LiBH4 MgH2 decreases from 350 to 300 °C and hydrogen released content enhances from 55 to 87% of the theoretical capacity. The sample containing ACNF releases hydrogen following a two-step mechanism with reversible hydrogen storage capacities up to 4.5 wt % H2 and 41.8 gH2 /L, whereas the sample without ACNF shows a single-step decomposition mainly from MgH2 with only 1.8 wt % H2 and 15.4 gH2 /L. Significant kinetic improvement observed in the doped system is due to the enhancement of both hydrogen permeability and heat transfer through the pellet. Highlights: Compacted 2LiBH4 MgH2 doped with ACNF to improve H2 diffusion and heat transfer. Reduction of onset desorption temperature by 50 °C after doping with ACNF. Enhanced reversible capacities from 1.8 to 4.5 wt % H2 and 15.4 to 41.8 gH2 /L. Increase of H2 permeability and heat transfer by 10 and ∼1.5 times, respectively. Reduced E A by 67 kJ/mol with maintained mechanical stability upon cycling.